Improving the Efficiency of the Freight Forwarding Procedure for Oversized and Overweight Cargo Transport Services at Hoang Dai Trading Company Limited - Bui, Thi Ha Phuong (Vietnam-Korea University of Information and Communication Technology, 2025)
Bachelor thesis of Business Administration - Logistics and Digital Supply Chain Management; 2021-2025.